Letter (copy) : International Brigade - Tewson, Vincent
035-0122-001 International. HVT/AC/DT/54. 30th September, 1942. Mr. J. Marchbank, National Union of Railwaymen, Castle Priory, Wallingford, Berks. Dear Mr. Marchbank, INTERNATIONAL BRIGADE. Many thanks for your letter of 28th September in which you convey to me your Executive Council's request that an approach be made to official quarters on behalf of former members of the International Brigade to secure their release. For your information and to explain the position, I attach herewith an extract from the Official Report of the House of Commons for 1st October, 1941. I have examined the enclosure to your letter from the International Brigade Association. Efforts to deal with the matter on the lines of the Association's suggestions would presuppose relationships between the Governments in question on a more cordial plane than existed in the Autumn of 1941. You will appreciate that the position with regard to the relationships between the British (or United States) and Vichy Governments has certainly not improved since then. If, in the light of this explanation, your Executive Council still desire the matter to be raised with the General Council, probably you will let me know. Yours sincerely, Assistant Secretary. Statement. 292/946/35/122